2011
DOI: 10.1051/0004-6361/201016021
|View full text |Cite
|
Sign up to set email alerts
|

Cosmic ray impact on astrophysical ices: laboratory studies on heavy ion irradiation of methane

Abstract: Laboratory data of CH 4 ice radiolysis promoted by fast heavy ions are obtained by infrared spectroscopy (FTIR). CH 4 molecules are condensed on a CsI substrate at 15 K, and the ice layer is bombarded by 220 MeV 16 O 7+ ion beam. The ice thickness is thin enough to be traversed by projectiles at constant velocity close to the equilibrium charge state. The induced CH 4 dissociation gives rise to the formation of molecular species CH 3 , C 2 H 2 , C 2 H 4 , C 2 H 6 , and C 3 H 8 . Their formation and dissociatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
38
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(42 citation statements)
references
References 48 publications
4
38
0
Order By: Relevance
“…Specifically, the discovery of abundant C 2 H 6 in comet C/1996 B2 Hyakutake by Mumma et al [17] led them to suggest H atom addition to C 2 H 2 , acetylene, as a source of C 2 H 6 . We have confirmed that the sequence [18]:…”
Section: H 2 O and Hydrocarbon Experimentssupporting
confidence: 69%
See 1 more Smart Citation
“…Specifically, the discovery of abundant C 2 H 6 in comet C/1996 B2 Hyakutake by Mumma et al [17] led them to suggest H atom addition to C 2 H 2 , acetylene, as a source of C 2 H 6 . We have confirmed that the sequence [18]:…”
Section: H 2 O and Hydrocarbon Experimentssupporting
confidence: 69%
“…High stopping power interactions are more efficient to dissociate the matrix molecules and also, as a consequence, to produce new chemical species. The same average value n ∼ 3 / 2 , was observed as well as in experiments with pure HCOOH [40], pure CH 4 ices [18], and in the mixture H 2 O:H 2 CO for the H 2 CO molecule [39]. Measurements using other matrixes are being performed in order to verify if this law can be generalized.…”
Section: Discussionmentioning
confidence: 93%
“…The increase of the CH 4 molecules due to irradiation was followed through its FTIR peaks at 1302–3009 cm −1 . The A ‐values used were 5.1 and 6.4 × 10 −18 cm molecule −1 , respectively (Gerakines et al 1996; de Barros et al 2011). The column density determined after irradiation is N = 3.61 × 10 16 molecules cm −2 for the 1302 cm −1 band.…”
Section: Laboratory Resultsmentioning
confidence: 99%
“…A detailed description of the experimental apparatus can be found e.g. in Pilling et al (2010) and de Barros et al (2011). In the centre of a high vacuum chamber (10 −8 mbar), a closed cycle helium cryostat kept the CsI substrate at 15 K. The pure methanol sample (Aldrich, 99.9 per cent) was purified with several freeze‐thaw cycles to remove any volatile gas from the sample.…”
Section: Methodsmentioning
confidence: 99%
“…Among the ices studied are water ice and mixtures with carbon dioxide and ammonia (Pilling et al 2010b;Bordalo et al 2013), ammonia (Pilling et al 2010a), methanol (de Barros et al 2011b), and methane ices (de Barros et al 2011a). These studies report on extensive chemical transformation found in the irradiated samples.…”
Section: Introductionmentioning
confidence: 99%